Theoretical Approaches to Change Interventions, Selecting Appropriate Interventions: - Wahdi, Adi; Hayadi, B. Herawan; Yusuf, Furtasan Ali; Ambarsari, Yuke; Mulyadi, Dadi (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
Change intervention is a process that aims to help individuals, groups, or organizations to adapt to change where the major changes that occur in management are individuals and the environment is very influential in shaping a person's character. There are various theoretical approaches that can be used to design and implement change interventions. This article discusses some of the main theoretical approaches and provides guidance for selecting interventions that are appropriate to the context and objectives to be achieved. change interventions include behavioral, organizational and systems theories. This study aims to determine the theoretical approach to change interventions, choosing appropriate interventions, the goal of organizational development change leads to more effective personal relationships between managers and employees at all levels of the organization in order to remove barriers to interpersonal and group communication. Based on the explanation above, the background of writing this paper is to find out what is meant by organizational development change intervention, understand organizational development change intervention techniques, along with examples of organizational development change intervention cases in teaching organizations.